2016
DOI: 10.4172/2169-0022.1000251
|View full text |Cite
|
Sign up to set email alerts
|

Scratch Wear Resistance of TiALN And AlCrN Coated EN-353 Steel

Abstract: TiAlN and AlCrN coatings were deposited on mild steel (EN 353 steel) by cathodic arc evaporation technique. Coefficients of friction, critical load, adhesive and cohesive properties of these coatings were studied using scratch tester. Failure mode for coatings with thickness of 2 and 4 µm were studied using scratch channels and acoustic activities as basis. Studies presented relationship between progressive and in situ emission signals. AlCrN coating exhibited higher critical load as determined by the acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…Kejadian aus yang rendah pada mata pisau TC terlapisi AlCrN disebabkan oleh kekerasan dan suhu oksidasinya yang tinggi, serta koefisien gesekannya yang rendah. Hasil yang sama juga telah dilaporkan pada penelitian sebelumnya (Kumar et al 2014;Chandrashekhar et al 2016). Fenomena ini membuktikan bahan pelapis yang diaplikasikan pada permukaan substrat pisau TC dapat memberikan perlindungan pada mata pisau melalui perbaikan karakteristiknya.…”
Section: Hasil Dan Pembahasanunclassified
“…Kejadian aus yang rendah pada mata pisau TC terlapisi AlCrN disebabkan oleh kekerasan dan suhu oksidasinya yang tinggi, serta koefisien gesekannya yang rendah. Hasil yang sama juga telah dilaporkan pada penelitian sebelumnya (Kumar et al 2014;Chandrashekhar et al 2016). Fenomena ini membuktikan bahan pelapis yang diaplikasikan pada permukaan substrat pisau TC dapat memberikan perlindungan pada mata pisau melalui perbaikan karakteristiknya.…”
Section: Hasil Dan Pembahasanunclassified
“…Mechanical and tribological results show AlCrN coating possesses high hardness and excellent wear resistance than the TiAlN and AlTiN coatings against boundary lubrication (Özkan et al 2018). Chandrashekhar et al (2016) were deposited AlCrN and TiAlN coating on EN-353 steel, and they observed AlCrN coating has excellent mechanical and wear properties compare to TiAlN coating.…”
Section: Related Workmentioning
confidence: 99%